OpenStudy (anonymous):

Y - 4 = - (1)/(4) (x-0) I came up with: -4y + 16 = X I continued to Standard form (Ax+Bx=C); X-4y=16 book has: 4y-16 = -X X + 4y = 16

7 years ago
OpenStudy (shadowfiend):

Your first solution (\(-4y + 16 = X\)) is the same as theirs, they just chose to leave the negative sign on the X. Your second solution has a slight sign error -- you move the 16 over to the right and then the X to the left (here it is done with both their form of the equation and yours): \[\begin{align} 4y - 16 &= -x & -4y + 16 &= x \\4y + x &= 16 & -4y - x &= -16 \\x + 4y &= 16 & 4y + x &= 16 \end{align}\]

7 years ago